Eosinophilic esophagitis in individuals with sex chromosome aneuploidies: Clinical presentations and management implications. Issue 12 (5th November 2021) - Howell, Susan; Buchanan, Catherine; Davis, Shanlee M.; Miyazawa, Heather; Furuta, Glenn T.; Tartaglia, Nicole R.; Nguyen, Nathalie
Abstract: Background: Supernumerary sex chromosome aneuploidies (SCA) are common genetic conditions characterized by additional X or Y chromosome, affecting 1/500 individuals, with the most frequent karyotypes of 47, XXY (Klinefelter syndrome), 47, XXX (Trisomy X), and 47, XYY (Jacob syndrome). Although there is considerable phenotypic variation among these diagnoses, these conditions are characterized by the presence of overlapping physical, medical, developmental, and psychological features. Our interdisciplinary clinic's experience anecdotally supports previous published findings of atopic conditions, feeding difficulties, and gastroesophageal reflux to be more prevalent in SCAs (Bardsley et al., Journal of Pediatrics, 2013, 163, 1085; Samango‐Sprouse et al., The Application of Clinical Genetics, 2019, 12, 191; Tartaglia et al., Acta Paediatrica, 2008, 100, 851). Furthermore, we observed that many of these patients have also been diagnosed with eosinophilic esophagitis (EoE), an association not currently reported in the literature. Methods: We conducted a retrospective chart review of all 667 patients with SCA seen at a large tertiary care center to investigate the prevalence and presenting features of EoE. Results: Four percent of children with SCAs had a biopsy‐confirmed diagnosis of EoE, which represents an odds ratio of 32 (95% CI 6–185) when compared to the prevalence rates reported in the general population. Conclusion: Routine screening for EoE symptoms may be warranted for individuals with SCA and atopic conditions. Abstract : Sex chromosome aneuploidies (SCA) are common genetic conditions that may be associated with atopic conditions, including eosinophilic esophagitis (EoE). Confirmed EoE was found in 29/650 (4.5%) of youth with SCA, 32 (95% CI 6–185) greater risk than the general pediatric population. Patients with SCA are at risk and should be screened for EoE with age‐appropriate symptoms on a routine basis, as earlier diagnosis and treatment may minimize the severity of disease.